2005
DOI: 10.1387/ijdb.052016hm
|View full text |Cite
|
Sign up to set email alerts
|

Cdx2 specifies the differentiation of morphological as well as functional absorptive enterocytes of the small intestine

Abstract: Many transcription factors are involved in the molecular control of intestinal epithelial cell differentiation. We report in this study that the transcription factor Cdx2 functions to define absorptive enterocytes during intestinal epithelial differentiation. Cdx2 is expressed in the villi of the normal small intestine. Intestinal metaplasia, which expresses Cdx2, occurs as a pathological condition in gastric mucosa. We have previously established Cdx2 transgenic mice expressing Cdx2 exclusively in the gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…We have confirmed the previous in vitro studies on Dpp4 as a target gene of Hnf1a and b, demonstrating that its levels in vivo were severely affected in our Hnf1 mouse models (Erickson et al, 2000). In addition, Cdx2, a transcription factor involved in enterocyte differentiation (Mutoh et al, 2005;Suh and Traber, 1996), is known to control the expression of Muc2, a marker of goblet cells (Yamamoto, 2003). In our studies, we showed that Cdx2, a gene harbouring an Hnf1 binding site conserved throughout evolution, is defectively expressed in double-mutant mice and is a direct target of Hnf1a.…”
Section: Hnf1a -/-; Hnf1bsupporting
confidence: 90%
See 1 more Smart Citation
“…We have confirmed the previous in vitro studies on Dpp4 as a target gene of Hnf1a and b, demonstrating that its levels in vivo were severely affected in our Hnf1 mouse models (Erickson et al, 2000). In addition, Cdx2, a transcription factor involved in enterocyte differentiation (Mutoh et al, 2005;Suh and Traber, 1996), is known to control the expression of Muc2, a marker of goblet cells (Yamamoto, 2003). In our studies, we showed that Cdx2, a gene harbouring an Hnf1 binding site conserved throughout evolution, is defectively expressed in double-mutant mice and is a direct target of Hnf1a.…”
Section: Hnf1a -/-; Hnf1bsupporting
confidence: 90%
“…2D), indicating that this gene is an in vivo target gene of Hnf1 and that the differentiation program of enterocytes could be altered in our mouse mutant. In addition, Cdx2, a transcription factor involved in intestinal development and enterocyte maturation (Suh and Traber, 1996;Mutoh et al, 2005;Grainger et al, 2010), was downregulated in double-mutant mice (37% reduction) and slightly downregulated in single Hnf1a mutant mice (16% reduction; Fig. 2D).…”
Section: Hnf1 Controls Enterocyte Terminal Differentiationmentioning
confidence: 99%
“…However, accumulating evidence indicated that Cdx2 is also expressed in CAG-associated gastric intestinal metaplasia, Barrett's esophagus and some sections of gastric cancer (13,14,(19)(20)(21). In a Cdx2 transgenic mouse model, the overexpression of Cdx2 induces morphologically the occurrence of the intestinal metaplasia in gastric mucosa (19,22,23). Such ectopic expression of Cdx2 protein is considered an important initial factor or switching for intestinal metaplasia of gastric mucosa, and may modulate the differentiation process of intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the endoderm, Cdx factors are crucial for patterning the intestine along the AP axis as well as along the crypt-villus axis. Loss of mouse Cdx2 leads to development of gastric epithelium in more-posterior intestinal domains and, conversely, overexpression of Cdx2 or Cdx1 transforms gastric epithelium to an intestinal fate (Beck et al, 1999;Mutoh et al, 2004;Mutoh et al, 2005;Silberg et al, 2002). In light of their ability to transform epithelia, it is not surprising that both Cdx1 and Cdx2 have been studied intensively for their roles in gastric and intestinal cancers (Guo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%